PROBLEMS OF «GREEN» LOGISTICS WITHIN THE CONCEPT OF SUSTAINABLE TRANSPORTATION DEVELOMPENT (Journal of Economic Research & Business Administration, 2017)
The purpose of the study was to conduct a comparative cross-country analysis of indicators characterizing the problem of «green» logistics in the framework of sustainable development and to identify the main directions of its solutions for Kazakhstan on the basis of studying the experience of other countries. This problem was considered in relation to transport, as with the development of the economy and the growth of urban transport demand is growing, which entails huge gas emissions to the environment. The analysis revealed the interdependence of the various factors to the transport emissions to different countries of the world. Relation and intensity of factors was estimated by calculating the correlation and analysis of indicators. Based on the analysis and conclusions, the state approach to the implementation of the principles of sustainable development in different countries and Kazakhstan were discussed in this article.